Subject and Use Index (Bulletin of the Center for Children's Books, 2024)
In the case of subject headings, the subhead "stories" refers to books for the readaloud audience; "fiction," to those books intended for independent reading. Christmas; Strand; Zentner Canada—fiction: Duncan Cats—fiction: Knisley; McKay Chickens—stories: Rees Civil rights movement: Sortino Murder—fiction: Crowley; Johnson; McCauley; Pagano; Sumrow Music and musicians—stories: